2008
DOI: 10.1002/adma.200602895
|View full text |Cite
|
Sign up to set email alerts
|

Direct Gas‐Phase Synthesis of Heterostructured Nanoparticles through Phase Separation and Surface Segregation

Abstract: Heterostructured nanoparticles (NPs) offer great opportunities for applications in areas such as biomedicine, renewable energy, information processing, and data storage by virtue of their embedded multiple functionalities and enhanced magnetic, [1,2] optical, [3] and catalytic performance [4] arising from the interactions of the individual components within the NPs.To understand the fundamental nature of these interactions, as well as to utilize them more efficiently, it is imperative to develop synthesis meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 33 publications
0
86
0
Order By: Relevance
“…The different effect of CO on the formation of nanocrystals of pure Pt and Pt-M alloys could be due to the phenomenon of surface segregation. [90][91][92][93] Studies have demonstrated that the surface composition of Pt-M alloy nanocrystals could be varied by changing the synthesis. The adsorption of methylamine on the surface of the as-prepared Pt octapods was indeed detected by FT-IR spectroscopy.…”
Section: Amine-assisted Synthesis Of Pt Nanocrystals With Highindex Fmentioning
confidence: 99%
“…The different effect of CO on the formation of nanocrystals of pure Pt and Pt-M alloys could be due to the phenomenon of surface segregation. [90][91][92][93] Studies have demonstrated that the surface composition of Pt-M alloy nanocrystals could be varied by changing the synthesis. The adsorption of methylamine on the surface of the as-prepared Pt octapods was indeed detected by FT-IR spectroscopy.…”
Section: Amine-assisted Synthesis Of Pt Nanocrystals With Highindex Fmentioning
confidence: 99%
“…16 These characteristic properties offer another dimension to design and control M-Au NCs structures by engineering the particle size, composition and atomic configuration. 17 Among different approaches, doping heterometals (e.g., Fe, Co and Ni) into Au NCs not only warrants reducing the consumption of the noble material, but also promises to endow distinctive properties benefitting from the synergistic effects. 18 Aiming at the controllable syntheses and the promising applications of M-Au binary NCs, it is paramount important to investigate their thermal stability dynamics dependence on the composition and structure configuration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Co-Au NCs with distinctively different heterostructures were synthesized and their magnetic properties can be tuned by metal thermal diffusion with programming the deposition temperature. 17 Au@Co NCs have been demonstrated with a morphology transformation from initial core-shell into a stable "peanut" structure during the heating, 19 while Ni-Au nanospindles were developed along a wrapping diffusion of Au component after heating treatments. 20 The Au-rich surface in Fe-Au NCs was formed upon high temperature annealing in vacuum ambient.…”
Section: Introductionmentioning
confidence: 99%
“…1) A surface segregation effect also contributes to maintain the core-shell morphology. 23) A similar alloy formation has been observed in a TEM column where small hemispherical particles (with less than 10 nm) on substrates accept post-impinging atoms at ambient temperature. 24,25) Such instantaneous alloying is accelerated for element combinations having negative mixing enthalpies.…”
Section: Discussionmentioning
confidence: 55%